1999
DOI: 10.2535/ofaj1936.76.4_171
|View full text |Cite
|
Sign up to set email alerts
|

SEM Study on the Dorsal Lingual Surface of Microtus Montebelli

Abstract: The dorsal lingual surface of Microtus montebelli was examined by scanning electron microscopy (SEM). The filiform papillae were distributed over the entire dorsal surface of the tongue. The filiform papillae notably differed in morphology by their location on the tongue and could be classified into 4 types: 1) simple conical papillae, 2) true filiform papillae, 3) giant conical papillae, and 4) saw-like papillae. The fugiform papillae were present rounded bodies scattered over the anterior dorsal surface of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
0
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 14 publications
4
32
0
3
Order By: Relevance
“…Unlike the agouti (Ciena et al 2013), capybara , nutria (Emura et al 2001), large vesper mouse (Watanabe et al 1997), Japanese dormouse (Kubota and Togawa 1966) and American beaver (Shindo et al 2006), where filiform, fungiform, foliate and vallate papillae were described, the dorsal lingual surface of the tongue in a degu bore filiform, conical and vallate papillae. Three types of the lingual papillae were reported also in the Middle East blind mole rat (Kilinc et al 2010).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Unlike the agouti (Ciena et al 2013), capybara , nutria (Emura et al 2001), large vesper mouse (Watanabe et al 1997), Japanese dormouse (Kubota and Togawa 1966) and American beaver (Shindo et al 2006), where filiform, fungiform, foliate and vallate papillae were described, the dorsal lingual surface of the tongue in a degu bore filiform, conical and vallate papillae. Three types of the lingual papillae were reported also in the Middle East blind mole rat (Kilinc et al 2010).…”
Section: Discussionmentioning
confidence: 95%
“…Filiform, fungiform, vallate and foliate papillae have been found in the agouti, Dasyprocta aguti (Ciena et al 2013), capybara, Hydrochaeris hydrochaeris , American beaver, Castor canadensis (Shindo et al 2006), nutria, Myocastor coypus (Emura et al 2001), large vesper mouse, Calomys callosus (Watanabe et al 1997), porcupine, Hystrix cristata ) and Japanese dormouse, Glirus japonicus (Kubota and Togawa 1966). Foliate papillae were absent in the Middle East blind mole rat, Spalax ehrenbergi (Kilinc et al 2010), Japanese grass vole, Microtus montebelli (Emura et al 1999) and squirrel, Sciurus vulgaris (Unsaldi 2010). Vallate papillae have not been revealed in the tongue of the guinea pig, Cavia porcellus (Sakr et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was a single vallate papilla on the tongue of the squirrel monkey (Iwasaki et al, 1988). There were two vallate papillae in the Japanese longfingered bat and nutria (Kobayashi and Shimamura, 1982;Emura et al, 2001b) while the long-nosed bat had four (Greenbaum and Philips, 1974). On the tongue of the bush dog, Emura et al (2000c) observed five vallate papillae.…”
Section: Discussionmentioning
confidence: 99%
“…In many animals, the Fu are scattered almost uniformly among the Fi, mainly on the anterior part of the lingual body (Emura et al, 1999a(Emura et al, , b, c, 2000a. In this study, the Fu are scattered among the Fi on the anterior 2/3, exepted for the midportion of the anterior 1/3 of the tongue.…”
Section: Discussionmentioning
confidence: 99%